CHALLENGES AND OPTIONS IN THE TREATMENT OF FEMORAL FRACTURES IN THE ELDERLY: AN INTEGRATIVE LITERATURE REVIEW (CIPEEX, 2024)
Femoral fractures in the elderly pose a significant challenge to public health. This integrativeliterature review shows that older patients with proximal femur fractures face numerousdifficulties, including high mortality rates, adverse events, and limited mobility recovery.Advanced age and frailty emerge as significant risk factors for unfavorable outcomes, resultingin high morbidity, mortality, and associated costs. Furthermore, most of these elderlyindividuals become institutionalized, experiencing significant mobility loss and decreasedindependence in daily activities. The choice between surgical and non-surgical treatment iscomplex and involves multiple factors, such as life expectancy, quality of life, costs, and patientpreferences. In this perspective, the aim of this study is to analyze different managementstrategies and their respective prognoses for femur fractures in elderly patients. Thisintegrative review was conducted through searches in the Public Medicine database and theVirtual Health Library, using various combinations of Health Science Descriptors, such as"Femoral Fractures," "Frail Elderly," and "Prognosis." Inclusion criteria encompassed freeoriginal articles published within the last 5 years and written in English. Texts unrelated to theresearch theme or objective were excluded. It was analyzed six studies related to the treatmentof proximal femur fractures in elderly and frail patients, covering various clinical aspects, costs,and multidisciplinary co-management protocols. Regarding treatment options, the choicebetween surgical and non-surgical treatment must be carefully considered. While surgicaltreatment may lead to a slight improvement in the quality of life, the associated costs aresignificantly higher, raising questions about cost-effectiveness. Additionally, the importance ofshared decision-making and the careful selection of patients are emphasized. The involvementof specialists in geriatric care is crucial in the treatment decision-making process. Other studiesexplored implant options for non-displaced femoral neck fractures, such as the triple screwconstruct and dynamic hip screw, which showed similar prognoses, and the femoral necksystem, which appeared promising in terms of surgical time and resistance to shearing forces.However, all treatment methods resulted in some fracture impaction and proximal femurshortening, suggesting the need for further research to confirm these findings. Furthermore,an observational study pointed to lower mortality rates in patients with distal femur fractureswho underwent total knee arthroplasty, especially among younger patients. This finding mayinfluence treatment approaches in specific cases. From another perspective, multidisciplinaryco-management proved effective in reducing the average hospitalization time, decreasinginpatient medical expenses, and reducing mortality. However, the long-term impact on medicalexpenses was not statistically significant, emphasizing the need for additional studies withlarger samples and longer observation periods. In conclusion, this integrative review providesa comprehensive overview of the challenges and treatment options for elderly patients withproximal femur fractures. Treatment choices should consider not only clinical outcomes butalso costs, patient preferences, and individual characteristics such as age, frailty, and lifeexpectancy. Multidisciplinary approaches and shared decision-making play a crucial role inimproving prognosis and managing costs related to this type of injury.
Keywords: fraturas de fêmur; idoso fragilizado; prognóstico